Pensamento teórico e formação docente: apropriação de saberes da tradição lúdica na perspectiva da teoria da formação das ações mentais por etapas de P. Ya. Galperin - Almeida, Luiz Ricardo Ramalho de (2011)
The study investigated the possibility of organizing a didactics unit for formation of hability of identifying and explaining the popular traditional games in the process of licensed formation in physical education. Had basic premised, the thesis formulated by Piorte Yakovleviche Galperin that the fundamental condition that mode determines the student s way of thinking and the theoretical structures thought. Is given by the method of organization activity that form the basis of guiding skills assimilates from this assumption the study defended the thesis that the contents of popular traditional games can be organizeds according the systemic functional-structural focus. As a method to plan a didactics unit that contributes to development of theoretical thought and the professional development of graduates in physical education. In this sense the general goal was studied and develop a training proposal of ability to identify and explain the popular traditional games for physical education teachers oriented to contribute to the development of theoretical thought. In the construction process of the thesis in a first moment was determined the invariant conceptual of popular traditional games from the method of analysis of activity, after was organized the content of popular traditional games according to the structural-functional systems revealing the essential properties elements and levels of relationship.These procedures provided to the construction elements of the concept popular traditional games, and was the basis for planning a didactical unit to the formation of ability to study. These strategies enable to build a set of prepositions to argue, as a result of the increases in the knowledge of the professional formation in physical education. The study was introduced the fallowing contributions; formulated a teaching proposal to develop the ability to identify popular traditional games, as a cultural and historical contribution and the development of an individual, in initial formation of physical education teacher, attuned to the demands of training and use of knowledge that requires this level of education, defined and organized the knowledge of popular traditional games , this enables a teaching able to raise the cognitive abilities and the theoretical concept of personality of graduated in physical education